Dyke-Davidoff-Masson Syndrome Without Motor Deficits: A Case Report Highlighting Diagnostic Challenges - Devasia, Joel; Nobbay, Esha; J, Karthik; J, Madhusudan (Journal of Neonatal Surgery, 2025)
Background: Dyke-Davidoff-Masson syndrome (DDMS) is a rare condition characterized by cerebral hemiatrophy, calvarial thickening, and neurological deficits, typically secondary to early cerebral injury. Classical presentations include seizures, hemiparesis, and cognitive impairment, though atypical cases without motor deficits have been reported. Case Report: A 19-year-old male presents with a long history of recurrent generalized seizures and cognitive impairment. Neurological examination revealed no focal motor deficits or hemiparesis. Brain imaging demonstrated marked left cerebral hemiatrophy, ipsilateral ventricular dilatation, prominent sulci, asymmetric calvarial thickening, and hyperpneumatization of the right frontal sinus, confirming DDMS despite the absence of motor weakness. Discussion: This case highlights an atypical DDMS presentation without hemiparesis, expanding the phenotypic spectrum of the syndrome. The absence of motor deficits may be attributed to selective non-motor cortical involvement or compensatory neuroplasticity during early brain development. The imaging findings of left cerebral atrophy, ventricular enlargement, and ipsilateral osseous changes are pathognomonic for DDMS and likely reflect chronic hemispheric volume loss due to perinatal or childhood vascular insult. Notably, the seizure semiology and cognitive impairment align with prior reports, reinforcing the role of functional reorganization in masking motor deficits. This case also underscores the diagnostic challenge in patients without classic hemiparesis, necessitating a high index of suspicion when neuroimaging reveals unilateral cerebral atrophy. Conclusion: This atypical presentation of Dyke-Davidoff-Masson syndrome without hemiparesis expands the recognized phenotype. Persistent refractory epilepsy and cognitive deterioration should prompt high-resolution neuroimaging for definitive diagnosis, individualized antiseizure-psychotropic regimens, and early multidisciplinary neurorehabilitation. Mitigating pharmacological interactions, socioeconomic constraints, and caregiver burden through cost-effective, integrated strategies may significantly enhance long-term functional outcomes.